2018
DOI: 10.1007/s12325-018-0840-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Drug Switching and Discontinuation Rates in Patients with Nonvalvular Atrial Fibrillation Treated with Direct Oral Anticoagulants in the United States

Abstract: IntroductionContinuous usage of direct oral anticoagulants (DOACs) among nonvalvular atrial fibrillation (NVAF) patients is essential to maintain stroke prevention. We examined switching and discontinuation rates for the three most frequently initiated DOACs in NVAF patients in the USA.MethodsPatients who initiated apixaban, rivaroxaban, or dabigatran (index event/date) were identified from the Pharmetrics Plus claims database (Jan 1, 2013–Sep 30, 2016, includes patients with commercial and Medicare coverage) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 28 publications
(41 reference statements)
5
25
0
Order By: Relevance
“…21 However, the data on the prescribing pattern of apixaban complement our other findings in that we have observed before that of the DOACs, apixaban is generally prescribed to older patients with greater comorbidity and higher stroke and bleeding risks. 11,21,22 Among the elderly patients with NVAF in the current study who were prescribed DOACs, after adjusting for the differences in patient characteristics, those treated with rivaroxaban and dabigatran had a 2-fold and nearly a 4-fold higher risk, respectively, to switch to another OAC than patients treated with apixaban. The relative risks of switching to another OAC are consistent with that of our previous study of younger patients with NVAF, although the unadjusted rates of switching among the elderly study population were numerically higher.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…21 However, the data on the prescribing pattern of apixaban complement our other findings in that we have observed before that of the DOACs, apixaban is generally prescribed to older patients with greater comorbidity and higher stroke and bleeding risks. 11,21,22 Among the elderly patients with NVAF in the current study who were prescribed DOACs, after adjusting for the differences in patient characteristics, those treated with rivaroxaban and dabigatran had a 2-fold and nearly a 4-fold higher risk, respectively, to switch to another OAC than patients treated with apixaban. The relative risks of switching to another OAC are consistent with that of our previous study of younger patients with NVAF, although the unadjusted rates of switching among the elderly study population were numerically higher.…”
Section: Discussionsupporting
confidence: 68%
“…The relative risks of switching to another OAC are consistent with that of our previous study of younger patients with NVAF, although the unadjusted rates of switching among the elderly study population were numerically higher. 21 For elderly patients treated either with apixaban or rivaroxaban, warfarin was the most frequent OAC switched to, while of those treated with dabigatran, the most frequent OAC switched to was apixaban. In addition to which DOAC was initiated, the regression analysis indicated that the risk for switching to another OAC may have been influenced by the geographic region of care and having significant comorbidity (CCI ≥5).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other European countries have reported either highly comparable,32 notably higher17 or lower15 18 1-year NOAC discontinuation rates based on a 30-day treatment gap,18 60-day treatment gap17 32 or other definition of discontinuation,15 with differences possibly attributable to differences in study size, design and/or composition of the study population (eg, the inclusion of OAC-naïve users only). One-year NOAC discontinuation rates among patient populations with NVAF reported from claims database studies in USA have been substantially higher,21 33 yet are consistent with a trend of higher discontinuation for dabigatran compared with rivaroxaban or apixaban,13 15 17 21 22 32 33 and of rates lowest for apixaban in most,13 15 17 21 33 although not all,22 studies. Most other studies on NOAC discontinuation have reported rates over shorter time periods 34…”
Section: Discussionmentioning
confidence: 62%
“…These findings suggest good tolerability and confidence in this class of medication in the UK. Comparable NOAC switching rates have been reported in two large US claims database studies,14 33 while in another large US administrative database among 34 022 OAC-naïve patients with NVAF, nearly 20% switched medication 36. Switching rates among other European NVAF cohorts starting NOAC therapy have been notably higher.…”
Section: Discussionmentioning
confidence: 78%
“…Prior studies have shown that geriatric conditions, including cognitive impairment, frailty, and depression, are associated with a higher odds of not being prescribed OAC despite being eligible (40, 41); however, few studies have examined relations between geriatric conditions and type of OAC selected (42, 43). We hypothesized that older, frailer participants affected by a greater burden of geriatric conditions would be prescribed VKA, since these conditions are associated with renal impairment, polypharmacy, and other age-related factors that affect DOAC treatment.…”
Section: Discussionmentioning
confidence: 99%